Study of embryotoxic effects of intranasally administred desloratadine on laboratory animals. - Alekhina Т. А.; Turkina V. А.; Grushka О. І. (Medicni Perspektivi, 2017)
The study was conducted to detect possible changes in embryogenesis and negative effects of third generation antihistamine – desloratadine – after intranasal administration of 1.3 mg/m3 and 13.0 mg/m3 of the substance to laboratory animals during their prenatal period. In these circumstances, desloratadine does not cause any significant changes of embryogenesis parameters. Macroscopic examination of the fetus and placenta in animals of experimental groups did not reveal any pathology or physiological deviations from the norm. 13.0 mg/m3 concentration of the drug caused a decrease in the weight of embryos in comparison with control group of animals and physiological data, despite a well developed, without visible pathology, placenta. This necessitates an in-depth study of possible teratogenic effects of intranasally administred desloratadine to laboratory animals.